Pharmacokinetics and Safety of Two Voriconazole Formulations after Intravenous Infusion in Healthy Korean Volunteers - Cho, Sang-Heon (Infect Chemother, 2020)
BACKGROUND: Voriconazole, a triazole antifungal agent exhibits broad-spectrum antifungal activity. It is used to treat severe, invasive fungal infections, including invasive aspergillosis and candidemia. The aim of this study was to assess the pharmacokinetic equivalence of a test formulation (Vorico(®) Injection) and reference formulation (Vfend(®) IV) of voriconazole. MATERIALS AND METHODS: This was a randomized, open-label, single-dose, three-group, two-treatment, two-sequence, two-period, crossover phase I trial with 7-day washout periods (ClinicalTrials.gov identifier NCT02631954). Twenty-four healthy Korean male subjects were recruited. In each group, eight subjects were randomized in a 1:1 manner to receive a single dose of 200 mg test or reference formulation intravenously over 1.5 h. Blood samples were collected over 24 h post-dose, and plasma drug concentrations were determined by liquid chromatography-tandem mass spectrometry. Pharmacokinetic parameters were determined using a non-compartmental analysis, and safety was evaluated. RESULTS: Twenty-three subjects completed the study. The geometric mean ratio (90% confidence interval) of the test formulation to reference formulation was 0.9570 (0.8178 – 1.1199) for the maximum plasma concentration (C(max)) and 1.0720 (1.0262 – 1.1198) for the area under the concentration–time curve from dosing to the last quantifiable concentration (AUC(last)). The mean plasma concentration–time profiles, pharmacokinetic parameters, and safety were comparable between the two formulations. CONCLUSION: Equivalent pharmacokinetic characteristics that satisfied the criteria of bioequivalence and similar safety profiles were observed for both test and reference formulations of voriconazole.